2009
DOI: 10.1590/s0100-879x2009005000032
|View full text |Cite
|
Sign up to set email alerts
|

The six-minute walk test and body weight-walk distance product in healthy Brazilian subjects

Abstract: We assessed the 6-min walk distance (6MWD) and body weight x distance product (6MWw) in healthy Brazilian subjects and compared measured 6MWD with values predicted in five reference equations developed for other populations. Anthropometry, spirometry, reported physical activity, and two walk tests in a 30-m corridor were evaluated in 134 subjects (73 females, 13-84 years). Mean 6MWD and 6MWw were significantly greater in males than in females (622 ± 80 m, 46,322 ± 10,539 kg . m vs 551 ± 71 m, 36,356 ± 8,289 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
215
8
63

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(314 citation statements)
references
References 26 publications
17
215
8
63
Order By: Relevance
“…The outcome was the distance traveled, and the test with the higher value was selected. The distance was expressed in absolute values and as percentages of the predicted values 22 .…”
Section: Six-min Walk Test (6-mwt)mentioning
confidence: 99%
“…The outcome was the distance traveled, and the test with the higher value was selected. The distance was expressed in absolute values and as percentages of the predicted values 22 .…”
Section: Six-min Walk Test (6-mwt)mentioning
confidence: 99%
“…Original Article studies are reported in Table 1. In particular, two equations [29,31] had been specifically developed for obese subjects, while in other eight studies [18,26,[35][36][37][38][39][40] both obese (BMI ≥30 kg/m 2 ) and non-obese subjects were enrolled. In four papers [20,25,34,41] no information was available with respect to the presence or absence of obese subjects in the study sample.…”
Section: Identification Of Prediction Equations For the Six-minute Wamentioning
confidence: 99%
“…Variables included in the equation R 2 Alameri H et al [35] Age, Height 0.25 Ben Saad H et al [36] Gender, age, weight, height 0.77 Camarri B et al [37] Gender, age, weight, height 0.36 Capodaglio P et al [29] Gender, age, BMI 0.48 Casanova C et al [40] Age, height, weight, HR 0,38 Chetta A et al [34] Gender, age, height 0.42 Enright PL & Sherrill DL [18] Gender, age, weight, height (or BMI) 0.42 M, 0.38 F Enright PL et al [20] Gender, age, weight, height 0.20 Gibbons WJ et al [25] Gender, age 0.41 Iwama AM et al [38] Gender, age 0.30 LarssonUE et al [31] Gender, height, BMI, final HR, HR at rest, 0,71 Masmoudi K et al [41] Gender, age, weight, height 0.60 Poh H et al [39] Age, weight, height, hearth rate 0.78 Troosters T et al [26] Gender, age, weight, height 0.66…”
Section: Studymentioning
confidence: 99%
“…The distances covered during the 6MWT, which appropriately reflect the physical capacity to perform daily tasks, were registered for analyses [22][23][24] . The test was carried out, following the procedures and recommendations of the American Thoracic Society 25 , which were adapted to the Brazilian Portuguese language 26 .…”
Section: Six-minute Walk Testmentioning
confidence: 99%